露光装置、露光方法、決定方法、および物品製造方法 (2022)
【課題】小フットプリント化と高スループット化の両立に有利な技術を提供する。【解決手段】露光装置は、基板１５を保持して移動する基板ステージ１６と、原版９における照明領域を規定する視野絞り５と、前記基板ステージおよび前記視野絞りを制御する制御部３とを有し、前記制御部は、フルショット領域を露光する場合、前記フルショット領域に前記複数のチップパターン領域が投影されるように前記基板ステージおよび前記視野絞りを制御し、パーシャルショット領域を露光する場合、前記パーシャルショット領域におけるチップ領域に対応するチップパターン領域に替えて前記欠けている一部のチップ領域に対応するチップパターン領域が前記パーシャルショット領域に投影されるように前記基板ステージを制御するとともに、前記パーシャルショット領域の隣のフルショット領域が遮光されるように前記視野絞りを制御する。【選択図】図１ A subject of the present invention is to provide a technique that is advantageous when established with small footprint and high yield. An exposure apparatus comprising: a substrate station, which moves while holding a substrate; a field of view aperture, which is defined in the illumination area of the original plate; and a control unit, which controls the substrate station and the field of view aperture. The plurality of irradiated areas of the substrate includes all of the irradiated areas having a plurality of wafer areas and a partial irradiated area that is located in the peripheral portion of the substrate and lacks a part of the plurality of wafer areas. In the case of exposing all the aforementioned irradiated areas, the control unit: controls the substrate station and the field of view aperture so that the plurality of wafer pattern areas are projected on all the irradiation areas; and in the case of exposing the aforementioned partial irradiated area, controls the substrate station so that the wafer pattern area corresponding to the wafer area of the missing part is projected on the partial irradiated area instead of the wafer pattern area corresponding to the wafer area in the partial irradiated area, and at the same time the aforementioned field of view aperture is controlled so that all the illuminated areas beside the aforementioned partial illuminated area are blocked from light.